The Identity of Meaning in the Translated Texts - Kaur, Lovleen (JOURNAL OF ADVANCES IN LINGUISTICS, 2013)
Translation is basically a process of conveying meaning or meaning of a given-linguistic discourse of a language into other language, more than just transferring words or grammatical structure of the Source Language (SL). The meaning of a word or set of words can be well understood because of its role in the whole linguistic expression in where they occur. For this reason, the meaning of a word is not only determined by the referred object or idea, but it is also governed by the use of the words or phrases in a certain way, context, and effects. The translator struggles to convey the exact meaning as there are no exact matches for words or expressions across languages. Moreover words have symbolic meanings attached to them.